DETERMINASI KONSUMSI LISTRIK DI INDONESIA - Stefanus Johan; Ari Mulianta Ginting (Media Ekonomi, 2022)
Indonesia’s actual electricity consumption is lower than was projected, at the same time there are new power plants under construction and some are ready to be commissioned and enter to the grid this year, oversupply of electricity is occurred and will create another burden to PT PLN (Persero). This study aims to examine the determinant factors of electricity consumption in Indonesia with emphasis on Gross Regional Domestic Product (GRDP), population, inflation, electricity tariff, number of customer and electrification ratio. The study uses panel data from the Electricity Supply Business Plan of PLN, the time series annual data is available for the period of 2011 to 2020 and the cross-section data represents regional of PLN such as Sumatera, Jawa-Madura-Bali, Kalimantan, Sulawesi and Maluku-Papua-Nusa Tenggara. Ordinary Least Square (OLS) method is used to estimate the significant of each independent and to select the most appropriate model, Chow test and Hausman test were conducted. The study chooses the most suitable econometric model which is Fixed Effect Model (FEM). The estimation from OLS suggests that GDRP, Population, Population, Number of customer and Electrification ratio are significant and positively impacted to electricity consumption while electricity tariff and inflation are also significant but negatively impacted to electricity consumption.